1997
DOI: 10.1177/002215549704500404
|View full text |Cite
|
Sign up to set email alerts
|

Localization of the Transmembrane 4 Superfamily (TM4SF) Member PETA-3 (CD151) in Normal Human Tissues: Comparison with CD9, CD63, and α5β1 Integrin

Abstract: SUMMARYIt has recently been shown that several members of the tetraspan superfamily, including CD9 and CD63, associate with each other and with ␤ 1 integrins. In this study, we examined the distribution of a recently identified tetraspan, PETA-3 (CD151), and of CD9, CD63, ␣ 5 ␤ 1, and the integrin ␤ 1 chain in normal human tissues by the indirect immunoperoxidase and alkaline phosphatase-anti-alkaline phosphatase techniques. PETA-3 showed a broad distribution and was expressed by endothelium, epithelium, Schwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
167
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(176 citation statements)
references
References 31 publications
6
167
2
1
Order By: Relevance
“…Although initially identified as a platelet/leukocyte surface glycoprotein, CD151 is expressed in a wide variety of tissues and cell types including megakaryoctes, endothelial cells, and myocytes (Fitter et al 1995(Fitter et al , 1998Hasegawa et al 1997). We present here the first observations on the regional distribution of CD151 transcripts in rat brain, which is in marked contrast to that reported in earlier studies which showed very low level of expression in mouse and human brain (Sincock et al 1997;Hasegawa et al 1997). The presence of CD151 mRNA in rat brain is unlikely due only to expression in the vascular endothelial compartment because the transcripts are also present at high levels in cultured cortical neurons.…”
Section: Discussioncontrasting
confidence: 89%
See 1 more Smart Citation
“…Although initially identified as a platelet/leukocyte surface glycoprotein, CD151 is expressed in a wide variety of tissues and cell types including megakaryoctes, endothelial cells, and myocytes (Fitter et al 1995(Fitter et al , 1998Hasegawa et al 1997). We present here the first observations on the regional distribution of CD151 transcripts in rat brain, which is in marked contrast to that reported in earlier studies which showed very low level of expression in mouse and human brain (Sincock et al 1997;Hasegawa et al 1997). The presence of CD151 mRNA in rat brain is unlikely due only to expression in the vascular endothelial compartment because the transcripts are also present at high levels in cultured cortical neurons.…”
Section: Discussioncontrasting
confidence: 89%
“…We present here the first observations on the regional distribution of CD151 transcripts in rat brain, which is in marked contrast to that reported in earlier studies which showed very low level of expression in mouse and human brain (Sincock et al 1997;Hasegawa et al 1997). The presence of CD151 mRNA in rat brain is unlikely due only to expression in the vascular endothelial compartment because the transcripts are also present at high levels in cultured cortical neurons.…”
Section: Discussioncontrasting
confidence: 89%
“…We observed the decrease in the expression of CD151, which is well known to be an important molecule for invasion and metastasis of tumors (25). It is also reported that CD151 associates with the integrin family and modulates cell adhesion (33,34). Our data indicate the effectiveness of PPARg antagonists in the prevention of squamous cell carcinoma invasion via the down-regulation of cell surface adhesion molecules.…”
Section: Discussionsupporting
confidence: 66%
“…20,21 Other integrins (a5b1, a6b1, a6b4 and aIIbb3) are also known to interact with CD151 depending on cell types, [22][23][24][25] although information about the binding sites is not available. Since CD151 is located at the periphery of the thin invasive protrusions (invadopodia) of cancer cells and treatment of the cells with anti-CD151 monoclonal antibody inhibits metastasis, 26 this molecule is considered to play an important role in invasion and metastasis.…”
mentioning
confidence: 99%